2011
DOI: 10.1177/0022466911419015
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Personnel Utilization in Inclusion-Oriented Schools

Abstract: Implementing research-based curricula and instruction in inclusion-oriented schools is helped or hindered by having coherent models of service delivery accounting for the full range of student diversity. The current investigation offers data from 174 participants in 32 schools, analyzed using descriptive statistics, correlation, and hierarchical linear modeling (HLM). The findings offer replication of special education service delivery data from an earlier study, new descriptive data, and HLM analyses that ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 26 publications
2
68
0
Order By: Relevance
“…Providing individualized and small group instruction to students with disabilities and managing student behaviours appeared to be the major instructional roles of TAs (Cameron, 2014;Carter et al, 2008;Gibson et al, 2014;Fisher & Pleasants, 2012;Harris & Aprile, 2015;Hughes & Valle-Riestra, 2008;Patterson, 2006;Webster & Blatchford 2013). For example, Webster et al (2010) analyzed the timelogs of TAs, which showed that TAs typically spent more than 50% of the school day performing individualized and small group direct pedagogical roles with students with disabilities, and Suter and Giangreco (2008) and Giangreco, Suter and Hurley (2013) reported that their TAs spent approximately 75% of their time delivering instruction and providing behavioural supports, respectively. Two studies reported that TAs also are involved in teaching larger groups of students (Patterson, 2006;Suter & Giangreco, 2008).…”
Section: Research Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing individualized and small group instruction to students with disabilities and managing student behaviours appeared to be the major instructional roles of TAs (Cameron, 2014;Carter et al, 2008;Gibson et al, 2014;Fisher & Pleasants, 2012;Harris & Aprile, 2015;Hughes & Valle-Riestra, 2008;Patterson, 2006;Webster & Blatchford 2013). For example, Webster et al (2010) analyzed the timelogs of TAs, which showed that TAs typically spent more than 50% of the school day performing individualized and small group direct pedagogical roles with students with disabilities, and Suter and Giangreco (2008) and Giangreco, Suter and Hurley (2013) reported that their TAs spent approximately 75% of their time delivering instruction and providing behavioural supports, respectively. Two studies reported that TAs also are involved in teaching larger groups of students (Patterson, 2006;Suter & Giangreco, 2008).…”
Section: Research Questionmentioning
confidence: 99%
“…Other factors identified as negatively impacting the performance of TAs are feeling underappreciated (Brown & Stanton-Chapman, 2014;Symes & Humphrey, 2011) and underpaid (Fisher & Pleasants, 2012;Patterson, 2006), having heavy workloads (Deveechi et al, 2012), and receiving little supervision from teachers (Giangreco, Suter, & Hurley, 2013).…”
Section: Research Questionmentioning
confidence: 99%
“…Educating children with SEN in the mainstream/general education classroom is an increasingly preferred option in many countries for reasons associated with equity; children with additional needs have an entitlement to the same high quality education, provided by appropriately trained teachers, as their peers (Giangreco et al, 2011). There has been a wealth of discussion around instruction in inclusive classes, notably exploring the concept of 'inclusive pedagogy'.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Giangreco et al, (2011) report that up to three quarters of the instruction for children described as having SEN was provided by TAs. In the UK, one in five (19%) interactions involving pupils with high level SEN are one-to-one interactions with TAs (Webster & Blatchford, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This approach is: (a) disruptive to the rest of the class; (b) usually disconnected to the general education curriculum in the class; (c) socially detrimental EQUITY-BASED INCLUSIVE SYSTEMS CHANGE 16 and stigmatizing to the student, since the aide is likely to get in the way of naturally occurring interactions among peers; and (d) turns over educational responsibility, for the most part, to unqualified personnel. Giangreco, Suter, and Hurley (2011) set forth a structural deployment model of paraprofessionals for whole-school, inclusive practices that is a good fit, in my opinion, with a human-capabilities, school-reform approach to equity-based inclusion. Paraprofessionals in this approach in the U.S. are assigned to grade-level and/or content area classrooms, not to individual students.…”
Section: Implications For Paraprofessionals and Teaching Assistantsmentioning
confidence: 99%